Noncovalent interactions between organometallic metallocene complexes and single-walled carbon nanotubes. - Sceats, E; Green, J (2006)
First principles density functional pseudopotential calculations have been used to investigate the nature of interactions between single-walled carbon nanotubes (SWNTs) and intercalated transition metal metallocene complexes, M(eta-C(5)H(5))(2) (MCp(2)). Three composites, MCp(2)-graphene (d(t)=infinity), MCp(2)@(17,0) (d(t)=1.33 nm), and MCp(2)@(12,0) (d(t)=0.94 nm) (where M=Fe,Co), have been studied to probe the influence of the nanotube diameter (d(t)) on the nature and magnitude of the interactions. Theoretical results presented here demonstrate that these MCp(2)@SWNT composites are stabilized by weak pi-stacking and CH...pi interactions, and in the case of the CoCp(2)@SWNT composites there is an additional electrostatic contribution as a result of charge transfer from CoCp(2) to the nanotube. The extent of charge transfer (MCp(2)-->SWNT) can be rationalized in terms of the electronic structures of the two fragments, or more specifically, the relative positions of the metallocene highest occupied molecular orbital and the conduction band of the nanotube in the electronic structure of the composite.